2022
DOI: 10.1002/ctm2.727
|View full text |Cite
|
Sign up to set email alerts
|

The central role of a two‐way positive feedback pathway in molecular targeted therapies‐mediated pyroptosis in anaplastic thyroid cancer

Abstract: Background Anaplastic thyroid carcinoma (ATC) is one of the most aggressive tumours. We previously confirmed that apatinib has potential therapeutic effects on ATC via regulated cell death (RCD). As a newly identified RCD, pyroptosis demonstrates direct antitumour activity different from apoptosis or autophagy. Therefore, the clinical significance, regulatory role and underlying mechanisms of pyroptosis in ATC were focused on in this study. Methods In a phase II trial, patients with anaplastic or poorly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Antiproliferative as a kind of important feature in apatinib has been addressed by researchers. For example, Zhijian (80). Our previous study indicated that after apatinib treatment ER stress could induce autophagy in colorectal cancer cell lines through the IRE1a pathway.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiproliferative as a kind of important feature in apatinib has been addressed by researchers. For example, Zhijian (80). Our previous study indicated that after apatinib treatment ER stress could induce autophagy in colorectal cancer cell lines through the IRE1a pathway.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Mechanistically, upregulated cleaved caspase-1 activated caspase-3 by generating GSDMD-N terminal, while cleaved caspase-3 enhanced caspase-1 activation which could induce pyroptosis by GSDME-N and vice versa. These processes constitute a unique system involving two-way positive feedback regulation ( 80 ). Our previous study indicated that after apatinib treatment ER stress could induce autophagy in colorectal cancer cell lines through the IRE1α pathway.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…The model showed a significant increase in tumor immune cell infiltration in the low-risk group. Zhao et al identified a novel antitumor effect of pyroptosis induced by the combination of apatinib and melittin in anaplastic THCA [ 33 ]. The distinct effects of pyroptosis in different thyroid diseases reflect complex molecular regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Melittin, an isolated water-soluble peptide derived from honeybee venom, is used to alleviate chronic inflammation [155]. Apatinib, in the presence of melittin, induces recruitment and activation of inflammatory vesicles and leads to pyroptosis and enhanced antitumor effects of apatinib [156]. This suggests that apatinib in mesenchymal or invasive TC shows promising therapeutic benefits.…”
Section: Pyroptosis and Thyroid Diseasementioning
confidence: 99%
“…Furthermore, low-dose apatinib synergistically achieves comparable therapeutic potential with melittin, thereby reducing adverse events. The positive feedback modulation may improve the therapeutic efficacy of antiangiogenic targeted agents, offering new prospects for targeted therapy [156].…”
Section: Pyroptosis and Thyroid Diseasementioning
confidence: 99%